Effect of leaf spraying with some vital and organic fertilizers and boron and zinc elements on the productivity and quality of Golden Delicious apple fruits. - Al Mohammed , Kinda; Makled, Mahmoud; Haddad, Wael (Journal of agricultural, environmental and veterinary sciences, 2017)
This study was conducted during 2015 within the research station Barshine Hama, which lieson a line length of 39O latitude 34O and rises 975 meters above sea level, on trees of Golden delicious apple cultivar on full fruiting stage,16 years old and budded on seed rootstock (Malus domestica), in order to study the effect of foliar spray of  bacteria PPFM, amino acid, humic acid, boron, and zinc, etch one alone in productivity and some apple quality parameters, the results have been shown a scientific rise in apple productivity on trees were spread with bacteria PPFM and boron compare with the rest of treatments, and this increase also coincided with a significant increase in total soluble solids, but without a significant change in firmness compared with rest of the treatments.
Keywords: Apple; Bacteria PPFM; Boron; Zinc; Amino acid; Humic acid